math

posted by .

Expess y as a function of x. C is a positive number.

1n y= 3x + ln C

Make both sides of the equation powers of e.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look like so.... x^2(x+3) adam, there's a slight problem with your notation in the expression y = f(x+3). Ordinarily we wouldn't put an expression in place of a variable, …
  2. Math

    4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now divide both sides of the equation by 4 and you will find out what the value of j is. Whenever you perform the same mathematical operation on both sides of an equation, …
  3. math

    can anyone help me with these 3 problems I am trying to check my daughters hoime work it has bee na few years. 1. The sum of n and twenty -two, multiplied by three, is 78 2. the product of z and 17 is less than or equal to the difference …
  4. math

    express as a function. c is a positive number ln y= 1n x + 1n C Make both sides of the equation an exponent of e. Remember that x^a * x^b = x^(a+b)
  5. MATH PLEASE CHECK IT!!2

    m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m - 5) * (m + 5)/(m - 2) = -1 (m - 2) cancels out in both the numerator and denominator on the left-hand side since you are multiplying. That leaves us with this: (m + 5)/(m - 5) …
  6. science

    rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i add 3x to both sides which makes it 3x - 6y = 9 then do i divide both sides by 9 or wat?
  7. maths

    i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be y = 4t + 9/7 ?
  8. math

    Rewrite the equation 4x – 6y = –30 as a function of x. Subtract 4x from both sides of the equation. Then divide both sides by -6. You should end up with an equation for y, as a function of x.
  9. Math

    Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + 35 What operation solves the equation for m?
  10. Math, Algebra

    81^3(x+1)=9^2(x-1) Solve this equation by expressing both sides as powers of 3.

More Similar Questions